Recidivism rates of female offenders discharged from forensic psychiatric treatment - Mayer, Juliane; Wolf, Viviane; Steiner, Ivonne; Dudeck, Manuela; Klein, Verena; Streb, Judith; Franke, Irina (Frontiers in Psychiatry, 2025)
ObjectiveRecidivism rates comprise an essential component in comprehensive risk assessment and should reflect the specific reference group of the individual being assessed. For female offenders with mental disorders, recidivism rates are nearly nonexistent. The goal of this study is to report offense- and disorder-related recidivism rates for the understudied group of female offenders discharged from forensic psychiatric treatment.MethodThe sample consisted of 525 German patients released from placement orders according to Section 63 (n = 110) or 64 of the German Criminal Code (n = 415), indicating a diagnosis of a serious mental disorder or substance use disorder, respectively. In a retrospective design, we analyzed archived patient files as well as official reconviction records.ResultsWith average times at risk of 8.5 and 5.3 years for each placement order, we observed general recidivism rates of 19% and 46%, and violent recidivism rates of 8% and 12%. Offense-related recidivism rates showed high numbers for property offenders, threateners, and arsonists. Disorder-related recidivism rates revealed that a comorbidity of schizophrenia and alcohol use disorder increased the risk of general reoffending eightfold (Exp[B] = 8.167; p = .025), while a comorbid substance use disorder and personality disorder heightened the violent recidivism risk fourfold (Exp[B] = 4.204; p = .029). Subgroup analysis of patients with substance use disorders indicated that treatment dropouts were about three times more likely to recidivate than patients who completed treatment (Exp[B] = 2.863; p <.001).ConclusionThe results provide rare recidivism data for risk assessment of female offenders with mental disorders and underscore the protective effect of forensic psychiatric treatment, including forensic aftercare, on recidivism.